Comparative Analysis of Essential Oil Profiles From Emprit Ginger Rhizome (Zingiber officinale var. amarum) Grown in Different Locations and Antibacterial Activity Againts Staphylococcus aureus - Styawan, Anita Agustina; Purwanto; Susidarti, Ratna Asmah; Windarsih, Anjar; Rohman, Abdul (Institute of Topical Disease Universitas Airlangga, 2024)
Indonesia, as a tropical country, boasts significant biodiversity, particularly regarding its flora and fauna. The country's medicinal plants are one inherited natural resource passed down through generations. The